Method for homogenizing trace elements in copper alloy
After ball milling and cold isostatic pressure treatment, homogenization is performed in an electromagnetic induction heating furnace, which solves the problem of uneven distribution of trace elements in copper alloy, improves the mechanical and conductive properties of copper alloy, and optimizes the process flow Save costs.
Patent Information
- Application Number
- CN202411484043.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
AI Technical Summary
The uneven distribution of trace elements in copper alloys leads to material embrittlement, affecting its mechanical properties, thermal and electrical conductivity.
By selecting W, Cr, Zr, Ti powders and Cu powders according to the mass percentage, mixing them, and then performing cold isostatic molding after ball milling, and then melting and annealing and homogenizing treatment in an electromagnetic induction heating furnace to ensure the uniform distribution of trace elements.
The uniform distribution of trace elements in copper alloy is achieved, its strength, hardness, thermal conductivity and electrical conductivity are improved, and process optimization saves costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of homogenization treatment, and in particular relates to a method for homogenizing trace elements in a copper alloy. Background Art
[0002] Trace elements in copper alloys have a significant impact on their properties and applications. For example, the addition of W can significantly improve the strength, hardness, and resistance to welding of copper alloys, and the addition of Cr can significantly improve the strength, heat resistance, and corrosion resistance of copper alloys. However, the distribution of trace elements in some copper alloys is not uniform, which will lead to an increase in defects in the copper alloy, embrittlement of the material, and affect its mechanical properties. The vacancies generated by the defects will also greatly affect the thermal and electrical conductivity of the copper alloy. Therefore, homogenizing the distribution of trace elements in copper alloys, making the strengthening mechanism of each element on the copper alloy effective, and thus enhancing the performance of the copper alloy is of great significance to the development of the copper alloy production field.
[0003] At present, the homogenization treatment of alloys can be carried out through a homogenization furnace. The main process parameters are heating temperature and holding time. Homogenization is mainly achieved through atomic diffusion at high temperature. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a method for homogenizing trace elements in copper alloys, wherein the trace elements in the copper alloy prepared by the method are evenly distributed, effectively realizing the strengthening mechanism of each element, and improving the strength, hardness, thermal conductivity and electrical conductivity of the copper alloy.
[0005] The present invention provides a method for homogenizing trace elements in a copper alloy, comprising the following steps:
[0006] Selecting W powder 0.8-1.2%, Cr powder 0.5-0.8%, Zr powder 0.2-0.4%, Ti powder 0.15-0.3%, and the balance Cu powder according to mass percentage to obtain a mixed powder;
[0007] ball-milling the mixed powder to obtain ball-milled powder;
[0008] The ball-milled powder is formed by cold isostatic pressing to obtain a green body;
[0009] The blank is melted, annealed and homogenized to obtain a homogenized copper alloy.
[0010] Preferably, the temperature of the green body melting is 1000-1050° C., the holding time is 1-3 hours, and the time to heat up to the temperature required for the green body melting is 8-12 minutes.
[0011] Preferably, the temperature of the annealing and homogenizing treatment is 580-620° C., and the time is 110-130 min.
[0012] Preferably, electromagnetic induction heating is used to meet the temperature required for the blank melting and annealing homogenization treatment, and the magnetic field intensity of the electromagnetic induction heating is 0.1-10T.
[0013] Preferably, the ball milling speed is 100 to 300 rpm, and the ball milling time is 15 to 20 hours.
[0014] Preferably, the pressure of cold isostatic pressing is 190-210 MPa, and the mass of the ball-milled powder used in cold isostatic pressing is 10-15 g.
[0015] Preferably, the purity of W powder is above 99.5%, and the average particle size is less than 20μm; the purity of Cr powder is above 99.5%, and the average particle size is less than 50μm; the purity of Zr powder is 99.9%, and the average particle size is less than 50μm; the purity of Ti powder is 99.5%, and the average particle size is less than 20μm; the purity of Cu powder is 99.7%, and the average particle size is less than 50μm.
[0016] Preferably, the ball mill used in ball milling is a ZrO2 ball mill;
[0017] The mass ratio of the ball mill to the mixed powder is 10:1, and the diameter of the ball mill is 8 to 12 mm.
[0018] Preferably, the green body melting and annealing homogenization treatments are both performed under an argon atmosphere.
[0019] The present invention provides a method for homogenizing trace elements in a copper alloy, comprising the following steps: selecting W powder 0.8-1.2%, Cr powder 0.5-0.8%, Zr powder 0.2-0.4%, Ti powder 0.15-0.3%, and the remainder Cu powder by mass percentage to obtain a mixed powder; ball milling the mixed powder to obtain a ball milled powder; cold isostatic pressing the ball milled powder to obtain a blank; melting the blank, annealing and homogenizing to obtain a homogenized copper alloy. The internal trace elements of the copper alloy prepared by the above method provided by the present invention are evenly distributed, and the strengthening mechanism of each element can be effectively realized to improve the strength, hardness, thermal conductivity and electrical conductivity of the copper alloy. The hardness and tensile strength of the copper alloy reach 101-110HV and 695-711MPa, respectively, while the thermal conductivity and electrical conductivity are maintained at a high level of 341-360W / m·K and 81%-85%IACS. Compared with ordinary homogenization treatment process, it can be completed in a short time, greatly optimize the heat treatment process and save a lot of costs. DETAILED DESCRIPTION
[0020] The present invention provides a method for homogenizing trace elements in a copper alloy, comprising the following steps:
[0021] Selecting W powder 0.8-1.2%, Cr powder 0.5-0.8%, Zr powder 0.2-0.4%, Ti powder 0.15-0.3%, and the balance Cu powder according to mass percentage to obtain a mixed powder;
[0022] ball-milling the mixed powder to obtain ball-milled powder;
[0023] The ball-milled powder is formed by cold isostatic pressing to obtain a green body;
[0024] The blank is melted, annealed and homogenized to obtain a homogenized copper alloy.
[0025] The internal trace elements of the copper alloy prepared by the above method provided by the present invention are evenly distributed, and the strengthening mechanism of each element can be effectively realized, thereby improving the strength, hardness, thermal conductivity and electrical conductivity of the copper alloy. Compared with the ordinary homogenization treatment process, it can be completed in a short time, greatly optimizes the heat treatment process, and saves a lot of costs.
[0026] The present invention selects W powder 0.8-1.2%, Cr powder 0.5-0.8%, Zr powder 0.2-0.4%, Ti powder 0.15-0.3%, and the balance Cu powder by mass percentage to obtain a mixed powder. In the present invention, the purity of W powder is more than 99.5%, and the average particle size is less than 20μm; the purity of Cr powder is more than 99.5%, and the average particle size is less than 50μm; the purity of Zr powder is 99.9%, and the average particle size is less than 50μm; the purity of Ti powder is 99.5%, and the average particle size is less than 20μm; the purity of Cu powder is 99.7%, and the average particle size is less than 50μm.
[0027] After obtaining the mixed powder, the present invention ball-mills the mixed powder to obtain ball-milled powder. The ball mill used in the ball milling is a ZrO2 ball mill; the mass ratio of the ball mill to the mixed powder is 10:1, and the diameter of the ball mill is 8 to 12 mm. The rotation speed of the ball mill is 100 to 300 rpm, and the ball milling time is 15 to 20 hours. In a specific embodiment, the ball mill is a ZrO2 ball mill with a diameter of 8 mm, a ZrO2 ball mill with a diameter of 10 mm, or a ZrO2 ball mill with a diameter of 12 mm; the rotation speed of the ball mill is 200 rpm, 150 rpm or 300 rpm; and the ball milling time is 20 hours or 16 hours.
[0028] After obtaining the ball-milled powder, the present invention subjects the ball-milled powder to cold isostatic pressing to obtain a green body; the pressure of the cold isostatic pressing is 190-210 MPa, and the mass of the ball-milled powder used in the cold isostatic pressing is 10-15 g. In a specific embodiment, the mass of the ball-milled powder used in the cold isostatic pressing is 12 g or 15 g, and the pressure is 200 MPa.
[0029] After obtaining the blank, the present invention melts the blank, performs annealing and homogenization treatment, and obtains a homogenized copper alloy. The present invention preferably heats and melts the blank in an electromagnetic induction heating furnace. The temperature of the blank melting in the present invention is 1000-1050°C; the time to heat up to the temperature required for the blank to melt is 8-12 minutes. The time for the blank to melt and keep warm is 110-130 minutes. After melting, the present invention cools down and performs annealing and homogenization treatment; the temperature of the annealing and homogenization treatment is 580-620°C, and the time is 110-130 minutes.
[0030] The present invention uses electromagnetic induction heating to meet the temperature required for blank melting and annealing homogenization treatment, and the magnetic field strength of electromagnetic induction heating is 0.1-10 T. The temperature measuring device in the present invention is a thermocouple, which makes the temperature measurement in the furnace more accurate. In the present invention, the blank melting and annealing homogenization treatment are both carried out in an argon atmosphere.
[0031] The present invention performs EDS surface scanning on part of the copper alloy, compares the ratio of each element obtained by the scanning with the ratio of each element in the original powder, and thus determines that the elements are evenly distributed.
[0032] The present invention adopts GB / T 4340.1 to test the hardness of the copper alloy; the present invention adopts GB / T 228.1-2010 to test the tensile strength of the copper alloy; the present invention adopts ASTM C177 to test the thermal conductivity of the copper alloy; the present invention adopts GB / T 32791-2016 to test the electrical conductivity of the copper alloy.
[0033] In order to further illustrate the present invention, a method for homogenizing trace elements in a copper alloy provided by the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0034] Example 1
[0035] (1) Weigh 0.3 g W powder, 0.18 g Cr powder, 0.09 g Zr powder, 0.06 g Ti powder, and 29.37 g Cu powder.
[0036] (2) The prepared raw material powder and 300 g of ZrO2 ball mill with a diameter of 10 mm were placed in a stainless steel vacuum ball mill, and the mixture was milled at room temperature with a rotation speed of 200 rpm for 16 h.
[0037] (3) Weigh 15 g of the ball-milled alloy powder and subject it to cold isostatic pressing at a pressure of 200 MPa.
[0038] (4) After forming, the green body is placed in an electromagnetic induction heating furnace for heating and melting. The temperature is raised to 1030°C in 10 minutes and kept for 2 hours. The temperature is then lowered to 600°C and kept for 2 hours. The whole process is carried out under an argon atmosphere with a magnetic field strength of 10 T.
[0039] Finally, the copper alloy after magnetic field homogenization treatment was obtained. The copper alloy was subjected to EDS surface scanning to obtain the proportion of each element, which was compared with the proportion of each element in the original powder. If the difference between the scanning proportion of each element and the proportion of the original powder does not exceed 0.1%, it is considered that the trace elements are evenly distributed. The surface scanning results show that the proportions of W, Cr, Zr, Ti and Cu are 0.99%, 0.59%, 0.31%, 0.21% and 98.00% respectively, proving that the trace elements are evenly distributed in the alloy. The hardness and tensile strength of the copper alloy reached 110HV and 711MPa respectively, and the thermal conductivity and electrical conductivity were maintained at a high level of 360W / m·K and 85%IACS.
[0040] Example 2
[0041] (1) Weigh 0.36 g W powder, 0.24 g Cr powder, 0.12 g Zr powder, 0.09 g Ti powder, and 29.19 g Cu powder.
[0042] (2) The prepared raw material powder and 300 g of ZrO2 ball mill with a diameter of 8 mm were placed in a stainless steel vacuum ball mill, and ball milled at room temperature using an XGB2 model ball mill with a rotation speed of 150 rpm and a ball milling time of 20 h.
[0043] (3) Weigh 12 g of the ball-milled alloy powder and form it by cold isostatic pressing at a pressure of 200 MPa.
[0044] (4) After forming, the green body is placed in an electromagnetic induction heating furnace for heating and melting. The temperature is raised to 1050°C in 10 minutes and kept for 2 hours. The temperature is then lowered to 600°C and kept for 2 hours. The whole process is carried out under an argon atmosphere with a magnetic field strength of 10 T.
[0045] Finally, the copper alloy after magnetic field homogenization treatment was obtained. The surface scanning results showed that the proportions of W, Cr, Zr, Ti and Cu were 1.21%, 0.79%, 0.41%, 0.29% and 97.30% respectively, proving that the trace elements were evenly distributed in the alloy. The hardness and tensile strength of the copper alloy reached 108HV and 702MPa respectively, and the thermal conductivity and electrical conductivity were maintained at a high level of 341W / m·K and 81%IACS.
[0046] Embodiment 3:
[0047] (1) Weigh 0.4 g W powder, 0.25 g Cr powder, 0.1 g Zr powder, 0.075 g Ti powder, and 49.175 g Cu powder.
[0048] (2) The prepared raw material powder and 500 g of ZrO2 ball mill with a diameter of 12 mm were placed in a stainless steel vacuum ball mill, and ball milled at room temperature using an XGB2 model ball mill with a rotation speed of 300 rpm and a ball milling time of 20 h.
[0049] (3) Weigh 12 g of the ball-milled alloy powder and form it by cold isostatic pressing at a pressure of 200 MPa.
[0050] (4) After forming, the green body is placed in an electromagnetic induction heating furnace for heating and melting. The temperature is raised to 1050°C in 10 minutes and kept for 2 hours. The temperature is then lowered to 600°C and kept for 2 hours. The whole process is carried out under an argon atmosphere with a magnetic field strength of 10 T.
[0051] Finally, the copper alloy after magnetic field homogenization treatment was obtained. The surface scanning results showed that the proportions of W, Cr, Zr, Ti and Cu were 0.81%, 0.51%, 0.21%, 0.15% and 98.32% respectively, proving that the trace elements were evenly distributed in the alloy. The hardness and tensile strength of the copper alloy reached 101HV and 695MPa respectively, and the thermal conductivity and electrical conductivity were maintained at a high level of 358W / m·K and 84%IACS.
[0052] As can be seen from the above embodiments, the present invention provides a method for homogenizing trace elements in copper alloys, comprising the following steps: selecting W powder 0.8-1.2%, Cr powder 0.5-0.8%, Zr powder 0.2-0.4%, Ti powder 0.15-0.3%, and the remainder Cu powder by mass percentage to obtain a mixed powder; ball milling the mixed powder to obtain a ball milled powder; cold isostatic pressing the ball milled powder to obtain a blank; melting the blank, annealing and homogenizing to obtain a homogenized copper alloy. The internal trace elements of the copper alloy prepared by the above method provided by the present invention are evenly distributed, and the strengthening mechanism of each element can be effectively realized to improve the tensile strength, hardness, thermal conductivity and electrical conductivity of the copper alloy. The hardness and tensile strength of the copper alloy reach 101-110HV and 695-711MPa, respectively, while the thermal conductivity and electrical conductivity are maintained at a high level of 341-360W / m·K and 81%-85%IACS. Compared with ordinary homogenization treatment process, it can be completed in a short time, greatly optimize the heat treatment process and save a lot of costs.
[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for homogenizing trace elements in a copper alloy, comprising the following steps: Selecting W powder 0.8-1.2%, Cr powder 0.5-0.8%, Zr powder 0.2-0.4%, Ti powder 0.15-0.3%, and the balance Cu powder according to mass percentage to obtain a mixed powder; ball-milling the mixed powder to obtain ball-milled powder; The ball-milled powder is formed by cold isostatic pressing to obtain a green body; The blank is melted, annealed and homogenized to obtain a homogenized copper alloy.
2. The method according to claim 1, characterized in that The temperature of the green body melting is 1000-1050° C., the heat preservation time is 1-3 hours, and the time of heating to the temperature required for the green body melting is 8-12 minutes.
3. The method according to claim 1, characterized in that The temperature of the annealing and homogenizing treatment is 580-620°C, and the time is 110-130 minutes.
4. The method according to claim 1, characterized in that: Electromagnetic induction heating is used to meet the temperature required for the blank melting and annealing homogenization treatment, and the magnetic field intensity of the electromagnetic induction heating is 0.1-10T.
5. The method according to claim 1, characterized in that The ball milling speed is 100-300 rpm, and the ball milling time is 15-20 h.
6. The method according to claim 1, characterized in that The pressure of cold isostatic pressing is 190-210 MPa, and the mass of the ball-milled powder used in cold isostatic pressing is 10-15 g.
7. The method according to claim 1, characterized in that The purity of W powder is above 99.5%, and the average particle size is less than 20μm; the purity of Cr powder is above 99.5%, and the average particle size is less than 50μm; the purity of Zr powder is 99.9%, and the average particle size is less than 50μm; the purity of Ti powder is 99.5%, and the average particle size is less than 20μm; the purity of Cu powder is 99.7%, and the average particle size is less than 50μm.
8. The method according to claim 1, characterized in that The ball mill used in ball milling is ZrO2 ball mill; The mass ratio of the ball mill to the mixed powder is 10:1, and the diameter of the ball mill is 8 to 12 mm.
9. The method according to claim 1, characterized in that: The green body melting and annealing homogenization treatments were all carried out under argon atmosphere.
